Better models, better treatment? a systematic review of current three dimensional (3D) in vitro models for implant-associated infections - Brümmer, Neele; Doll-Nikutta, Katharina; Schadzek, Patrik; Mikolai, Carina; Kampmann, Andreas; Wirth, Dagmar; Hoffmann, Andrea; Pott, Philipp-Cornelius; Karras, Oliver; Auer, Sören; Stiesch, Meike (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionUnderstanding the biology of implant-associated infections is essential in order to provide adequate detection, prevention and therapeutic strategies. Advanced 3D in vitro models offer valuable insights into the complex interactions between cells and bacteria in the presence of implant materials. This review aims to give a comprehensive overview of current 3D in vitro models that mimic implant-associated infections.MethodsThe structured literature search initially identified 258 publications, seven of which fitted the inclusion criteria.ResultsThe included 3D models were established either to mimic the in vivo situation (organotypic model) or to investigate future implant materials. In three studies, organotypic models for dental implants were created and one study described an organotypic model containing immune cells. In the remaining three studies, biomaterials for constructing future orthopedic implants were developed and tested. All authors included specific cells and bacteria suitable for the respective implants. The dental implant models used fibroblasts and keratinocytes; the orthopedic implant models used stem cells and fibroblast-like cells; the model containing immune cells incorporated co-cultivation of fibroblasts and THP-1 derived macrophages. For bacterial challenge, most authors used Gram positive bacteria, but three studies employed Gram negative bacterial species. A wide variety of analytical methods of different complexity were applied after co-culture of cells and bacteria and between one and five different methods were used.DiscussionAll models could be employed to provide answers to specific scientific questions regarding implant-associated infections. Nonetheless, this review reveals the limitations of current 3D models for the investigation of implant-associated infections and highlights the opportunities for further development in this scientific field.